2019
DOI: 10.11613/bm.2019.030708
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent variation of ionized calcium in serum samples

Abstract: Introduction: The aim of this study was to compare ionized calcium (iCa) concentrations in arterial heparinized blood and venous serum and to investigate time-dependent variation of iCa in serum samples centrifuged and analysed at different times. Materials and methods: Ionized calcium was measured (N = 25) in arterial blood within 20 min after puncture, and in serum within 10 min after centrifugation conducted 30 min after sampling. Effect of time between sampling and centrifugation was examined in three tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They also found that delayed centrifugation of the samples leads to a significant decrease in IC. 15 …”
Section: Discussionmentioning
confidence: 99%
“…They also found that delayed centrifugation of the samples leads to a significant decrease in IC. 15 …”
Section: Discussionmentioning
confidence: 99%
“…1 Despite generally being considered a more accurate indicator of true calcium status compared to total calcium concentrations, concerns about the stringent pre-analytical requirements of measuring ionized calcium restricts its use in routine practice. 1,3,4 However, total calcium concentrations only provide an estimate of the biologically active portion of calcium based on the relationship between calcium and its binding partners. 5 Any changes to factors influencing this relationship, such as pH and albumin concentration, can affect total calcium measurements.…”
Section: Introductionmentioning
confidence: 99%